APPLICATION OF COPING STRATEGIES IN OVERCOMING STRESS IN COLLEGE STUDENTS WHILE WORKING AT THE FACULTY OF DA'WAH AND COMMUNICATION, STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Fitriana Fitriana; Ira Wirtati (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to identify the factors causing stress and the coping strategies used by students studying while working at the Faculty of Da'wah and Communication, State Islamic University of North Sumatra. This study uses a qualitative case study approach with six respondents selected through snowball sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The results revealed five main themes of stress sources: difficulty managing time, conflicting academic tasks, lack of family support, difficulty obtaining work permits, and an unsupportive work environment. Difficulty managing time emerged as the dominant factor experienced by all respondents. In responding to stress, students employed coping strategies: problem-focused coping, such as planning, discussing with superiors, and prioritizing, and emotion-focused coping, such as surrendering to God, seeking emotional support, and expressing emotions through relaxation activities. These findings emphasize the importance of time management skills, emotional regulation, and social support as psychological foundations for maintaining academic and work balance among working students.